Kebijakan Pemerintah Kabupaten Jember dalam Pencegahan Penyalahgunaan Bahu Jalan Sebagai Lahan Parkir - Effendy, Irgi Fahrezy; Ubaidillah, Lutfian (Indonesian Journal of Law and Justice, 2023)
The road shoulder is one of the spaces found on the road, the road shoulder is only intended as a special lane for emergency vehicles, but in Jember Regency it is misused and used as a parking area, resulting in disruption of the consistency of traffic flow. The authority of the Jember Regency Government in efforts to prevent the misuse of road shoulders as parking spaces has actually been regulated in Law Number 38 of 2004 concerning Roads. In this connection, the aim of this research is to answer what form the Jember Regency government policy takes in preventing misuse of road shoulders as parking spaces. This type of research is normative juridical, and the research method is taken through several approaches such as the statutory regulations approach, concept approach and case approach. The results of this analysis and discussion can be concluded that the policy of the Jember Regency government through interested agencies based on the regent's regulations which regulate the basis of authority and organizational structure is to carry out socialization and control as a form of effort to prevent misuse of road shoulders as parking lots, this is in accordance with what has been mandated in article 110 Government Regulation Number 34 of 2006 concerning Roads.